2021
DOI: 10.1371/journal.pone.0248543
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal modelling for the evaluation of an altered Indian saline Ramsar site and its drivers for ecosystem management and restoration

Abstract: Saline lakes occupy 44% and 23% of the volume and area of all lakes that are tending to suffer from extended dryness, reduced hydro period, or complete desiccation by 2025. The current study is conducted on Sambhar Salt Lake, the largest inland saline Ramsar, site of India, contributing to 9.86% of total salt production. The lake is under threat due to illegal salt pan encroachment, losing brine worth 300 million USD. The objective was to identify the key drivers that affect the lake at a landscape level. Geos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In past studies the wetland area showed continues decrease. In the study of (Naik & Sharma, 2021) SWI index detected more water area within all, but it seems that it detects muddy soil as water, which is not proper result we want, due to this for shallow lakes it is not the best suitable water indices. AWEIsh and MNDWI showed best result for such lakes.…”
Section: Discussionmentioning
confidence: 85%
“…In past studies the wetland area showed continues decrease. In the study of (Naik & Sharma, 2021) SWI index detected more water area within all, but it seems that it detects muddy soil as water, which is not proper result we want, due to this for shallow lakes it is not the best suitable water indices. AWEIsh and MNDWI showed best result for such lakes.…”
Section: Discussionmentioning
confidence: 85%